2017
DOI: 10.2136/sssaj2016.12.0439
|View full text |Cite
|
Sign up to set email alerts
|

Soil Health Indicators during Transition from Row Crops to Grass–Legume Sod

Abstract: Core Ideas Transition from organic row crop to 3‐yr sod led to significant changes in surface soil health. Changes in soil chemistry were generally subject to a manure × transition time interaction. Manure plus sod are required to increase organic matter in deficient soils. Soil quality and/or health changes with grass sod insertion in a rotation. Grass–Legume sod inclusion in row crop rotations changes soil health. The transition to a 3‐yr orchardgrass (Dactylis glomerata L.) and red clover (Trifolium pratens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The measurements of K, Ca, Mg, and Zn were comparable to those found in an agricultural soil at the organic farm in Monongalia Co., WV (Pena-Yewtukhiw et al, 2017). The measured P in this study was found to be lower than the P in the literature in both the agricultural system and mine soils (Roberts et al, 1988;Bendfeldt et al, 2001;Pena-Yewtukhiw et al, 2017). The measured K was similar to those found by Roberts et al (1988) and Bendfeldt et al (2001).…”
Section: Available Nutrientssupporting
confidence: 79%
“…The measurements of K, Ca, Mg, and Zn were comparable to those found in an agricultural soil at the organic farm in Monongalia Co., WV (Pena-Yewtukhiw et al, 2017). The measured P in this study was found to be lower than the P in the literature in both the agricultural system and mine soils (Roberts et al, 1988;Bendfeldt et al, 2001;Pena-Yewtukhiw et al, 2017). The measured K was similar to those found by Roberts et al (1988) and Bendfeldt et al (2001).…”
Section: Available Nutrientssupporting
confidence: 79%
“…The mechanisms regulating N uptake in response to C have been extensively studied in vitro (8,25). The complex regulatory network includes a specialized sigma factor (σ 54 ; rpoN), . CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that pasture enhances the organic matter inputs to the soil through below ground biomass or root exudation. A separate study of the soils from the OCLF experiment showed that SOM increased from the beginning to the end of the three-year period spent in pasture (Pena et al 2017). A study of root biomass growth in forage crops in eastern Canada found that root biomass doubled from the first to the second year of growth of perennial grasses and legumes, and that these forage crops had lower shoot to root ratios than annual crops (Bolinder et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of reduced ammonium availability and lower abundance of AOO contributes to greater potential for retention of nitrogen from organic sources. Additionally, pasture can develop soil structure and increase SOM, leading to improved stability and water infiltration and retention (Pena et al 2017). Implementation of practices such as pasture integrated crop rotation can help managers to maintain yields while preserving soil health and preventing environmental damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation